Synthesis and Inhibition Evaluation of New Benzyltetrahydroprotoberberine Alkaloids Designed as Acetylcholinesterase Inhibitors - de Lima, Bruna R.; Lima, Juliana M.; Maciel, Jéssica B.; Valentim, Carolina Q.; Nunomura, Rita de Cássia S.; Lima, Emerson S.; Koolen, Hector H. F.; de Souza, Afonso Duarte L; Pinheiro, Maria Lúcia B.; Cass, Quezia B.; da Silva, Felipe Moura A. (Frontiers in Chemistry, 2019)
Secondary metabolites from natural products are a potential source of acetylcholinesterase inhibitors (AChEIs), which is a key enzyme in the treatment of many neurodegenerative diseases. Inspired by the reported activities of isoquinoline-derivative alkaloids herein we report the design, one step synthesis and evaluation by capillary enzyme reactor (ICER) of benzyl analogs (1a-1e) of the tetrahydroprotoberberine alkaloid stepholidine, which is abundant in Onychopetalum amazonicum. Docking analysis based on the crystal structure of Torpedo californica AChE (TcAChE) indicated that π-π interactions were dominant in all planned derivatives and that the residues from esteratic, anionic and peripheral subsites of the enzyme played key interaction roles. Due to the similarities observed when compared with galantamine in the AChE complex, the results suggest that ligand-target interactions would increase, especially for the N-benzyl derivatives. From a series of synthesized compounds, the alkaloids (7R,13aS)-7-benzylstepholidine (1a), (7S,13aS)-7-benzylstepholidine (1b), and (S)-10-O-benzylstepholidine (1d) are reported here for the ﬁrst time. The on flow bioaffinity chromatography inhibition assay, based on the quantification of choline, revealed the N-benzylated compound 1a and its epimer 1b to be the most active, with IC50 of 40.6 ± 1 and 51.9 ± 1 µM, respectively, and a noncompetitive mechanism. The proposed approach, which is based on molecular docking and bioaffinity chromatography, demonstrated the usefulness of stepholidine as a template for the design of rational AChEIs and showed how the target-alkaloid derivatives interact with AChE.